Business and Industry World Contributions to Community Empowerment - Herwina, Wiwin; Mustakim, Mustakim (Universitas Negeri Semarang, 2019)
The development of the business and the industry world goes hand in hand with the development of education in society. Education plays an important role in improving people's life skills. The purpose of this study is to describe the contribution of the business world and the world of industry in community empowerment, and to describe the concept of community empowerment for alumni of the Yuwita training and course institution, Tasikmalaya City, West Java. This study uses a qualitative method with a descriptive approach. The techniques used in collecting research data are observation techniques, in-depth interviews, and documentation. Whereas for checking the validity of the data the researcher uses data validity criteria to support that this research has credibility, transferability, dependability, and confirmation. The results of the study illustrate that the business and the industry world (DUDI) contribute to the empowerment of alumni communities in courses and training in skin beauty. DUDI's contribution to community empowerment manifests itself in increasing independence, the formation of study groups, competencies that are in accordance with the Indonesian National Qualification Framework Standard (SKKNI). Increasing entrepreneurship based on regional potential, increasing skills, knowledge and attitudes. And increasing economic capacity, ability to access welfare benefits, and cultural and political abilities. A partnership between courses and training institutions with DUDI was realized. Collaboration in technology transfer, knowledge/skills transfer, human resource transfer, transfer of learning methods, and capital transfers, as well as business opportunities.